(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents the advantages of using the credit-module system in the most developed countries of the world and analyzes its use in teaching subjects in the education system of the Republic of Uzbekistan. The advantages of training using the credit-module system are described, and scientific and methodological recommendations are given. The credit-module system is aimed at independent learning of students, determines the amount of knowledge in the form of credit, creative assimilation of knowledge based on individual and group work, choice of educational trajectory with strict determination of the educational process. Independent education is an important and integral component of the educational process, which represents the opportunity for students to acquire independent knowledge, free theoretical and practical analysis of a subject, and have their own personal intellectual opinion on current problems and issues, scientific research. is of great importance in the formation of the necessary knowledge, understanding and skills related to free-thinking, the ability to develop conclusions and proposals on problematic issues and their implementation. A certain part of the knowledge, skills and qualifications defined in the scientific program of the subject “Inorganic Chemistry” of the student’s independent work must be mastered by the student on the basis of the advice and recommendations of a natural science teacher in the classroom and outside the classroom.